FACTORS INFLUENCING FINANCIAL STATEMENT FRAUD IN THE PENTAGON'S FRAUD PERSPECTIVE - Apriandy, Roynaldi Buwono; Widyastuti, Reni Dwi; Setiawan, Aris (Jurnal Akuntansi dan Keuangan (JAK), 2026)
Financial statement fraud is a serious problem in Indonesia, threatening investor confidence and damaging the integrity of public companies. This phenomenon causes huge losses for investors and stakeholders and erodes confidence in the capital market. This study aims to identify how the five elements of the fraud pentagon—pressure, opportunity, rationalization, capability, and arrogance—contribute to financial statement fraud. Using a quantitative approach, this study analyzes data from public companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2024. The sample was selected using purposive sampling, and the data were processed through logistic regression analysis using SPSS 30 software. The data used were obtained from annual financial reports, yielding 120 samples. The results indicate that only rationalization and capability are significant factors in fraud, while pressure, opportunity, and arrogance are not significant in financial statement fraud. In conclusion, this study confirms that the fraud pentagon is a comprehensive and useful framework for detecting potential fraudulent practices in financial statements. Therefore, companies are advised to invest in improving their internal control systems and ensuring effective supervision to prevent fraud.